Gestión administrativa para el desarrollo de la calidad operativa en la cooperativa de ahorro y crédito SUMAK KAWSAY La Mana, año 2015. - Panta Moreira, Mirna Jessenia (2015)
The research project was developed in the credit union Sumak Kawsay city of La Mana, aiming at designing a model of administrative management for the development of operational quality, for which survey was conducted targeting partners and staff of the institution in order to know the situation of the administrative and operational area of the company. In addition, a situational analysis was performed using the SWOT analysis, raising the concern to design a model that would achieve administrative efficiency and flexibility in each of the services offered by the bank, through strategies such as training workshops to improve the quality service; and the installation of a software that allows partners to notify their timely payments, resulting in not only the development of operational quality but also increased levels of profitability and quality services, contributing to economic development and Canton La Mana business and the province. Keywords: administrative management, operational quality, cooperative.